Removal of Pesticides from Aqueous Solutions by Adsorption on Zeolites as Solid Adsorbents - C. De Smedt; F. Ferrer; K. Leus; P. Spanoghe (Adsorption Science & Technology)
To prevent the contamination of groundwater and surface water by pesticides, appropriate measures should be taken to treat the contaminated water before discharge. Zeolites seem to be a promising material to adsorb pesticides. This paper deals with the removal of mobile pesticides from water on different types of zeolites. Experiments were performed to understand the adsorption mechanisms of bentazon, clopyralid, imidacloprid, isoproturon and metalaxyl-m on zeolites and to determine the most efficient adsorbent for the purification of water contaminated by these pesticides. More immobile pesticides (imidacloprid, isoproturon and metalaxyl-m) tended to associate with the zeolites, whereas more mobile pesticides (bentazon and clopyralid) partitioned in water. According to the adsorption percentage, zeolite of the types BEA and FAU showed the best results for adsorbing the pesticides. Two different kinetic models, namely, pseudo-first-order and pseudo-second-order models, were used to fit the kinetics data. The experimental data were best described by the pseudo-second-order model. The rate of adsorption was also in line with the mobility of the pesticides. The adsorption isotherms were determined and modelled based on the observed types according to International Union of Pure and Applied Chemistry. The type III isotherm was most frequently observed in this case. The Freundlich model, which describes this type of isotherm, gave a good fit for the adsorption of the pesticides. Different assumptions, that could describe the meaning of these type III isotherms, are discussed in this paper. These assumptions are based on the particle size of the adsorbates, the water adsorption on the zeolites and the modifications of the crystal structures.